A rough set-based knowledge discovery process - Zhong, Ning; Skowron, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The knowledge discovery from real-life databases is a multi-phase process consisting of numerous steps, including attribute selection, discretization of real-valued attributes, and rule induction. In the paper, we discuss a rule discovery process that is based on rough set theory.
Keywords: rough sets; KDD process; hybrid systems